PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE COLLEGE BALL TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XI IPS SMA ADABIAH 2 PADANG - Marjulisa, Rike; Rismen, Sefna; Mardiyah, Ainil (Pendidikan Matematika, 2014)
ABSTRACTÂ This research was conducted based on the fact indicating that the studentsâ understanding on mathematic concept was still low, the students seemed to be less active and unable to complete the tasks given by themselves. The aim of this research was to improve the studentsâ activity and understanding on mathematic concept by using College Ball strategy in class XI IPS of SMA Adabiah 2 Padang. This was an experimental research whose sample was chosen by random. The instruments of the research were observation sheets and a test on the studentsâ understanding on mathematicÂ  concept with reliability r11= 0,91. The result of the research revealed that after the strategy applied, the studentsâ activity improved, and their understanding on mathematicÂ  concept was better than that of students treating by using conventional learning strategy. This could be seen from the P-Value (0,001) which was smaller than Î± (0,05), Thus it was concluded that the use of College Ball strategy could improve the studentsâ understanding on mathematic concept better than that of the conventional learning.